Analysis of overvoltages in transformer windings with considering of distributed parameters - Seheda, Mykhaylo; Mazur, Tetyana; Chutora, Ivan (Видавництво Львівської політехніки, 2011)
The procedure of mathematical model forming intended for electromagnetic processes analysis in transformers when distributed parameters are taken into account is presented. Problems of calculation of the equivalent circuit parameters and solving of partial differential equations are discussed.
Keywords: transformer winding; distributed parameters; mathematical model